Optimasi Manajemen Rapat di Masa Pandemi Covid-19 Berbasis SeMaR - Ahmad Faisol; Joseph Dedy Irawan; Hirarki Ardi Pratama (Universitas Trunojoyo Madura, 2020)
The meeting activity is one of the routine and scheduled activities that is definitely carried out in every institution, as well as the ITN Malang campus. Problems arise when Covid-19 begins to plague in the city of Malang so that teaching and learning activities on campus must be closed and demanded to work from home according to government recommendations. Difficulties that arise are the way to send invitations and record the results of meetings that have not been efficient. So, it is necessary to develop an application that functions to manage meetings in the ITN Malang internal environment named SeMaR (Meeting Management System). This application was developed based on web and Android using design sprint development method. The results of the analysis and testing show that the design of applications that involve potential users can produce an application that is truly in accordance with user requirements. In addition, the use of the SeMaR application to manage meeting activities in the ITN Malang is able to optimize employee performance especially during the Covid-19 pandemic, and meeting management can be more effective and efficient.